Characterization of the Ngouache Landslide by Geotechnical Survey (Bafoussam, Cameroon) - Owoutou, P. Eba’a; Fokwa, D.; Tsala S., S. A. Zogo; Ekoro Nkoungou, H. L. (European Scientific Journal, ESJ, 2024)
The heavy rainfall during the night of October 28-29, 2019, caused a landslide in the Ngouache 4 neighborhood in Bafoussam in the West Cameroon region. This landslide caused 43 deaths, several missing persons and the destruction of several houses and plantations. The present investigation attempts to find the causesof this landslide. First, the landslide area was identified and heavy dynamic penetrometer surveys were conducted. Next, intact and reworked samples were taken and, finally, slopes were measured on the slide area to determine the soil parameters. The results of the heavy dynamic penetrometer showed the presence of altered clay layers which, when saturated, exert hydrostatic pressure and unbalance the soil. The granulometric analysis noted a soil with more than 50% of grains of ϕ>80µm with liquidity limits between (50-65.3%), a consistency index between (1.01-1.24), a low cohesion between (0.22-0.30 bars) for a high internal friction angle (20.72°-23.86°), slopes between 48° and 56° and a degree of saturation Sr between (80.5° and 139.9°). These characteristics associated with the large water columns of the night of October 28 to 29, 2019 demonstrated that the water had exerted a hydrostatic pressure having made the clay material reach the limit of plasticity to the creep and raised the level of the water table. Thistherefore promoted the saturation of the substrate yet the increase in the water content reduces the cohesion of the materials and that triggered the saturation at the origin of this deadly slide. The results of the present research may help the public authorities in the decision making regarding the characterization and the securing of risk zones.